2020
DOI: 10.1097/njh.0000000000000622
|View full text |Cite
|
Sign up to set email alerts
|

Acute Care Nurses' Experiences of Basic Palliative Care

Abstract: As the population of chronically ill, older adults increases, there is a growing need for palliative care. The Institute of Medicine recommends that health care providers have a basic competency in palliative care. However, the definition of basic palliative care in practice and providers' understanding of basic palliative care lack clarity. The purpose of this study was to describe nurses' perceptions of basic palliative care in the acute care setting. This was accomplished by conducting focus group and indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…This finding was in the same line with Nepal, et al (18) , who conducted a study in Lumbini, Nepal about "Clinical Nurses' Knowledge and Attitude on Palliative Care" and reported that two thirds of participants were from the age group less than 25 years with a mean ± SD of 25±5.42 years. Meanwhile this result was conversely with Neiman (19) who conducted a study in Mankato about "Acute care nurses' experiences of basic palliative care" and revealed that majority of nurses were between the ages of 30 and 56 years.…”
Section: Discussionmentioning
confidence: 76%
“…This finding was in the same line with Nepal, et al (18) , who conducted a study in Lumbini, Nepal about "Clinical Nurses' Knowledge and Attitude on Palliative Care" and reported that two thirds of participants were from the age group less than 25 years with a mean ± SD of 25±5.42 years. Meanwhile this result was conversely with Neiman (19) who conducted a study in Mankato about "Acute care nurses' experiences of basic palliative care" and revealed that majority of nurses were between the ages of 30 and 56 years.…”
Section: Discussionmentioning
confidence: 76%
“…1,3 Palliative surgery is an integral part of palliative care. 1,2,4 Palliative surgery is performed with the primary aim for relieving symptoms caused by an advanced disease or improving the quality of life. 4,5 Palliative surgery, which is as old as surgery itself, is mostly common and constitutes 10-20% of surgical oncology procedures.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Palliative surgery, which is as old as surgery itself, is mostly common and constitutes 10-20% of surgical oncology procedures. 2,4 Considering the palliative nature of these procedures performed for alleviating symptoms of non-neoplastic, progressive, and life-limiting diseases, the rate is much higher. 2,4 Palliative surgery is also frequently used for bleeding; obstruction and perforation; vascular access; effusion drainage; enteral nutrition; and pain control.…”
Section: Introductionmentioning
confidence: 99%
“…A confusão sobre os CP está associada á expectativa de vida a qualquer custo, falta de treinamento e uma cultura curativa presente nos profissionais que atuam na terapia intensiva. A execução de procedimentos invasivos na terapia intensiva vai prolongar a dor e o sofrimento, não trarão a cura para a doença principal, de modo que as ações paliativas não são apropriadas para este ambiente assistencial, onde a concepção de CP ainda se apresenta distante da premissa da unidade de cuidados intensivos (9)(10)(11)(12).…”
Section: Introductionunclassified